Comparación de las herramientas Splunk y Elk Stack, en cuanto a la facilidad de creación y personalización de informes para incidentes de seguridad y eventos críticos, en la generación de informes automatizados. - Mosquera Cedeño, Marcos Douglas (2025)
The research was carried out through in-depth analysis with the purpose of comparing the Splunk and Elk Stack tools in terms of ease of creating and customizing reports for security incidents and critical events, in order to evaluate their efficiency in the automated generation of reports in business environments. The study includes a comparative matrix based on the findings of the bibliographic review and bibliographic observation to order the research that allows making a list where the discoveries on usability and customization are archived, also in its greatest condition the precursors and analysts shared expressing that more than depending on the tool and its functionalities it depends on what the consumer wants, this is because both are of vital help if they are used in the appropriate field. In conclusion, they are strong tools that can help companies improve IT security, improve their operations and make wiser decisions. Despite some challenges, the potential implementation advantages are very important and can have a positive impact on society in general.